A low dielectric loss dicyclobutene resin, a preparation method and application thereof
Patent Information
- Application Number
- CN202611222272.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]然而BCB属于低沸点且易挥发的液体,工艺稳定性差,通常需要将BCB制备成衍生物,以便在实际应用中充分发挥其性能优势
本申请实施例提供的一种制备低介损双苯并环丁烯树脂的方法,该方法首先在甲苯中混合二烯基化合物、卤代苯并环丁烯、缚酸剂与第一催化剂以形成混合原料,其中,第一催化剂的组分为金属化合物与含膦基配体。借助金属化合物的高选择性及含膦基配体的分散作用,促使二烯基化合物与卤代苯并环丁烯充分发生交叉偶联反应,从而在苯并环丁烯单体中引入大位阻桥连基团R1。该基团能提高苯并环丁烯分子沸点,提高加工稳定性;且该基团能破坏苯并环丁烯分子的平面性,使得双苯并环丁烯树脂在加工温度下具有良好的流动性,彻底规避传统双苯并环丁烯树脂因熔融提前聚合的风险;同时,双苯并环丁烯树脂的低极性饱和结构还能提升其室温长期储存稳定性。此外,通过第一纯化处理与第二纯化处理,可彻底去除第一催化剂、第二催化剂残留等易引发预聚的杂质;且该方法全程在惰性氛围中进行,既避免了原料氧化,又能通过氢气氢化还原双苯并环丁烯树脂中的不饱和键,从根源上消除自发预聚与副反应隐患,进一步提高苯并环丁烯的加工稳定性。
Smart Images

Figure CN122977918A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of copper clad laminate resin materials technology, and in particular to a low dielectric loss bisbenzocyclobutene resin, its preparation method and application. Background Technology
[0002] With the rapid development of the information industry, the demand for smaller, thinner, higher-performance, and more multifunctional electronic products is increasing. This demand requires electronic components to develop towards higher density, higher precision, and higher integration. Simultaneously, it also requires electronic components to have higher signal propagation rates and signal transmission capacity. Closely related to these properties of electronic components is the dielectric property of copper-clad laminates (CCLs), and the key material for the dielectric property of CCLs is the matrix resin in the CCL material.
[0003] In high-frequency, high-speed copper-clad laminates used in artificial intelligence and computing, hydrocarbon resins with extremely low dielectric constants and dielectric losses are generally used as the matrix resin. Among many hydrocarbon resins, benzocyclobutene (BCB), as an active monomer with an all-hydrocarbon structure, has extremely low polarity and high reactivity. Under heating conditions or ultraviolet light, BCB can undergo ring-opening to form an o-methenquinone active intermediate. Subsequently, the o-methenquinone active intermediate generates oligomers and polymers through self-coupling reactions. It can also undergo Diels-Alder addition reactions with other dienophilic monomers to form a benzo six-membered ring structure. These curing processes do not require the addition of catalysts or initiators, do not produce volatile substances, and the resulting cured products have low dielectric constants, low moisture absorption, high thermal stability, and high chemical stability. This lays the foundation for the application of BCB in the field of electronic materials.
[0004] However, BCB is a low-boiling-point and volatile liquid with poor processing stability. Therefore, it is usually necessary to prepare BCB derivatives to fully utilize its performance advantages in practical applications. Currently, a common approach is to prepare fluorene derivatives with a single BCB structure. While this improves the stability of the BCB monomer, the fluorene-based BCB in the derivative has a high melting point and poor solubility, resulting in poor processing performance. Summary of the Invention
[0005] This application provides a low-dielectric-loss benzocyclobutene resin, its preparation method, and its application to solve the following technical problem: how to improve the processing stability of benzocyclobutene.
[0006] In a first aspect, embodiments of this application provide a method for preparing low dielectric loss bisbenzocyclobutene resin, the method comprising: A diene compound, a halobenzocyclobutene, an acid-binding agent, a first catalyst, and toluene are mixed to obtain a mixed feedstock; wherein, the first catalyst is a metal compound and a phosphine-containing ligand; In an inert gas atmosphere, the mixed raw materials are subjected to a cross-coupling reaction to obtain reactants; The reactants were subjected to a first purification process to obtain a bisbenzocyclobutenyl diene compound. In a first organic solvent, the bisbenzocyclobutene diene compound is subjected to a hydrogenation reaction and a second purification treatment using a second catalyst to obtain a low-dielectric-loss bisbenzocyclobutene resin.
[0007] Optionally, the amount of the diene compound n1, the amount of the halobenzocyclobutene n2, and the amount of the acid-binding agent n3 satisfy the following: n1:n2:n3=1:(2.1 to 2.3):(2.2 to 2.5).
[0008] Optionally, the amount of the metal compound n4 and the amount of the phosphine-containing ligand n5 satisfy: n4:n5 = 1:(2.4 to 6.0); and / or The amount of substance n4 of the metal compound and the amount of substance n1 of the dienyl compound satisfy the following: n4:n1 = (0.05 to 5.00):100.
[0009] Optionally, the dienyl compound includes at least one selected from the following: dicyclopentadiene, 4-vinyl-1-cyclohexene, 4,4'-divinyl-1,1'-biphenyl, 1,6-divinylnaphthalene, 1,5-divinylnaphthalene, 2,7-divinylnaphthalene, bisphenol A diallyl ether, bisphenol F diallyl ether, 1,2-bis(4-vinylphenyl)ethane, and 1,4-cyclohexanediethanol divinyl ether; and / or The halobenzocyclobutenes include at least one of 4-bromobenzocyclobutene, 4-chlorobenzocyclobutene, and 4-iodobenzocyclobutene; and / or The acid-binding agent includes at least one of pyridine, triethylamine, trimethylamine, sodium bicarbonate, potassium bicarbonate, sodium carbonate, and potassium carbonate; and / or The metal compound includes at least one of palladium chloride, rhodium chloride, palladium acetate, palladium dichloride of bis(triphenylphosphine), platinum chloride, platinum chlorate, palladium methacrylate, and bis(tributylphosphine)platinum chloride; and / or The phosphine-containing ligand is triphenylphosphine and / or tris(o-methylphenyl)phosphine; and / or The second catalyst includes at least one of the following: aluminum / nickel catalytic system, metallocene catalyst, platinum catalyst, rhodium catalyst, palladium catalyst, and transition metal catalyst supported on a support.
[0010] Optionally, the mass m1 of the second catalyst and the mass m2 of the bisbenzocyclobutenyl diene compound satisfy the following: m1:m2 = (0.01 to 3.00):100.
[0011] Optionally, the temperature of the cross-coupling reaction is 60°C to 100°C; and / or The hydrogenation reaction is carried out at a temperature of 20°C to 100°C, at a pressure of 0.1 MPa to 7.0 MPa, and for a time of 1 h to 10 h.
[0012] Secondly, embodiments of this application provide a low dielectric loss bisbenzocyclobutene resin, which is prepared by the method described in the first aspect, and has a molecular structure as shown in Formula 1. , Formula 1, In Formula 1, the R1 group is , , , , , , , At least one of them.
[0013] Thirdly, embodiments of this application provide a copper-clad laminate, wherein the raw material of the copper-clad laminate includes the bisbenzocyclobutene resin described in the second aspect, and by mass parts, the raw material of the copper-clad laminate includes: The composition includes: 100 parts of bisbenzocyclobutene resin, 0.6 to 1.5 parts of vinyl coupling agent, 0.01 to 0.20 parts of initiator, and 43 to 51 parts of filler.
[0014] Optionally, the vinyl coupling agent may include at least one of vinyltrimethoxysilane, vinyltriethoxysilane, and vinyltriphenoxysilane; and / or The initiator includes at least one of dicumyl peroxide, di-tert-butyl peroxide, and tert-butyl peroxide; and / or The fillers include at least one of the following: silicon dioxide, montmorillonite, magnesium oxide, aluminum oxide, mica powder, barium sulfate, kaolin, silicon nitride, boron nitride, zirconium oxide, aluminum nitride, graphite, titanium dioxide, talc, and iron oxide.
[0015] Fourthly, embodiments of this application provide a method for preparing the copper-clad laminate described in the third aspect, the method comprising: Dibenzocyclobutene resin, vinyl coupling agent, initiator and filler are mixed in a second organic solvent to obtain resin solution; The glass fiber cloth is impregnated with the resin solution to obtain impregnated glass fiber cloth; The impregnated glass fiber cloth is subjected to solvent removal to obtain impregnated fiber cloth; The impregnated fiber cloth is baked to obtain a semi-cured sheet; The multi-layered semi-cured sheets are sequentially stacked and copper foil is attached to obtain the copper-clad laminate precursor. The copper-clad laminate precursor is hot-pressed to obtain the copper-clad laminate; The baking temperature is 130°C to 170°C, and the baking time is 4 min to 7 min.
[0016] The technical solutions provided in this application have the following advantages compared with the prior art: This application provides a method for preparing low-dielectric-loss bisbenzocyclobutene resin. The method first involves mixing a dienyl compound, a halobenzocyclobutene, an acid-binding agent, and a first catalyst in toluene to form a mixed raw material. The first catalyst consists of a metal compound and a phosphine-containing ligand. Utilizing the high selectivity of the metal compound and the dispersing effect of the phosphine-containing ligand, the dienyl compound and the halobenzocyclobutene undergo a thorough cross-coupling reaction, thereby introducing a sterically hindered bridging group R1 into the benzocyclobutene monomer. This group increases the boiling point of the benzocyclobutene molecule, improving processing stability; furthermore, it disrupts the planarity of the benzocyclobutene molecule, resulting in good flowability of the bisbenzocyclobutene resin at processing temperatures, completely avoiding the risk of premature polymerization due to melting in traditional bisbenzocyclobutene resins; simultaneously, the low-polarity saturated structure of the bisbenzocyclobutene resin also enhances its long-term storage stability at room temperature. Furthermore, the first and second purification processes can completely remove impurities that can easily trigger prepolymerization, such as the residues of the first and second catalysts. Moreover, the entire process is carried out in an inert atmosphere, which not only avoids the oxidation of raw materials but also reduces the unsaturated bonds in the benzocyclobutene resin by hydrogenation, thereby eliminating the potential risks of spontaneous prepolymerization and side reactions from the source and further improving the processing stability of benzocyclobutene. Attached Figure Description
[0017] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.
[0018] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1 This is a schematic flowchart of a method for preparing low dielectric loss bisbenzocyclobutene resin provided in an embodiment of this application; Figure 2 This is a schematic flowchart of a method for preparing copper-clad laminates provided in an embodiment of this application. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0021] The range descriptions used in this application, such as numerical ranges and proportional ranges, include all possible sub-ranges and single numerical values within that range. For example, the range descriptions of "1 to 6" or "1~6" cover all sub-ranges (such as 1 to 3, 2 to 5, etc.) and single numbers (such as 1, 2, 3, 4, 5, 6) between 1 and 6. Unless otherwise specified, the terms "comprising" and others used herein mean "including but not limited to"; relational terms such as "first" and "second" are used only to distinguish different entities or operations and do not imply an actual order or relationship; "and / or" indicates that multiple situations can exist individually or simultaneously; expressions such as "at least one," "multiple," and "at least one" refer to any combination of the corresponding objects, including combinations of single or multiple objects. The proportional relationships involved in this document, such as mass ratios and molar ratios, should be understood as the correspondence between the first and second terms of a proportional formula, according to the order of description. The raw materials, reagents, instruments, and equipment used herein can all be obtained by purchasing from the market or by existing methods.
[0022] Figure 1 An exemplary schematic diagram of a method for preparing low dielectric loss bisbenzocyclobutene resin provided in an embodiment of this application is shown. like Figure 1 As shown in the embodiments of this application, a method for preparing low dielectric loss bisbenzocyclobutene resin is provided, the method comprising: S1. A diene compound, a halobenzocyclobutene, an acid-binding agent, a first catalyst, and toluene are mixed to obtain a mixed raw material; wherein, the first catalyst is a metal compound and a phosphine-containing ligand; S2. Under an inert gas atmosphere, the mixed raw materials are subjected to a cross-coupling reaction to obtain reactants; S4. The reactants are subjected to a first purification process to obtain a bisbenzocyclobutenyl diene compound; S5. In a first organic solvent, the bisbenzocyclobutene diene compound is subjected to a hydrogenation reaction and a second purification treatment using a second catalyst to obtain a low-dielectric-loss bisbenzocyclobutene resin.
[0023] It should be noted that the first purification process can be to first wash the reactants with water until neutral, then heat the reactants to remove water, then further remove impurities and water from the reactants through filtration and vacuum distillation, and finally obtain high-purity bisbenzocyclobutenyl diene compounds through crystallization and filtration.
[0024] It should be noted that the second purification process can involve filtering the hydrogenation product or washing it with pure water, and then subjecting the hydrogenation product to vacuum distillation to remove the solvent, ultimately obtaining high-purity, low-dielectric-loss bisbenzocyclobutene resin.
[0025] It should be noted that the first organic solvent can be toluene, xylene, cyclohexane, n-hexane, or n-heptane.
[0026] This application provides a method for preparing low-dielectric-loss bisbenzocyclobutene resin. This method systematically solves the processing stability problems of traditional benzocyclobutene (BCB) resin (strong crystallinity, melting temperature close to the ring-opening temperature, easy prepolymerization, narrow processing window, etc.) from two core dimensions: molecular structure design and preparation process control. The specific improvement mechanism is as follows: I. Core Mechanism: Identifying the pain points of BCB processing stability.
[0027] The core defects of traditional bis-BCB resins are: 1. High molecular rigidity and significant crystallinity, requiring high-temperature (>150℃) melt processing; 2. The ring-opening polymerization temperature of the four-membered ring in BCB is about 200℃. Pre-ring opening prepolymerization is very likely to occur during the melting process, resulting in a surge in viscosity and an extremely narrow processing window (only tens of degrees Celsius). 3. Impurities and unsaturated double bonds can easily trigger side reactions, leading to viscosity loss during the storage and processing of traditional double BCB resins.
[0028] This method solves the problems faced by traditional dual BCB resins at their root through structural design and process control.
[0029] II. Molecular structure design: fundamentally improving processing stability.
[0030] This method directly optimizes processing stability through a structural design of "double BCB units + specific bridging group R1 + saturation modification". 1. Reduce structural rigidity, disrupt crystallinity, and completely avoid premature melting and polymerization: (1) Introduce a bridging group R1 with large steric hindrance and moderate rigidity into the double BCB resin. The bridging group R1 can destroy the planarity and symmetry of BCB molecules and greatly reduce the crystallization ability. (2) The subsequent hydrogenation reaction can completely reduce the unsaturated double bonds in the bridge to saturated bonds, further weakening the intermolecular forces; (3) Ultimately, the processing temperature is much lower than the ring-opening temperature of the double BCB resin, which avoids the risk of premature polymerization during the melting process from the root and greatly widens the processing window.
[0031] 2. Regulate ring-opening activity to suppress viscosity runaway during processing: (1) Steric hindrance control: The large steric bridging groups form physical barriers between molecules, preventing BCB units from getting close to each other and inhibiting the intermolecular crosslinking rate after ring opening, so that the double BCB resin can maintain a low viscosity for a long time during processing (coating, molding, potting) and avoid sudden viscosity changes. (2) Electronic effect regulation: The bridging groups are weak electron-donating, neutral saturated alicyclic rings and substituted aryl groups, which will not overactivate the four-membered ring and avoid premature polymerization caused by excessively low ring-opening temperature; (3) Eliminate unsaturated side reactions: The saturated bridge after hydrogenation has no active double bonds, which eliminates the additional crosslinking caused by double bond self-polymerization at processing temperature and DA side reaction with BCB ring-opening alkenyl groups, thus avoiding abnormal increase in viscosity.
[0032] 3. Low polarity structure improves storage stability: The saturated bridging groups have low polarity and weak intermolecular forces, which not only achieves a liquid state but also reduces intermolecular prepolymerization, while reducing hygroscopicity, avoiding side reactions caused by moisture, and improving the stability of long-term storage at room temperature (no increase in viscosity, no prepolymerization).
[0033] III. Preparation process control: Eliminating hidden dangers and ensuring structural stability.
[0034] Precise control of process steps ensures product structure and eliminates impurities and side reactions that affect processing stability. 1. Highly selective cross-coupling + rigorous purification to avoid impurity-catalyzed prepolymerization: (1) The “metal compound + phosphine ligand” catalytic system (e.g., Pd catalyst, typical Suzuki / Heck coupling reaction) is adopted to highly selectively graft double BCB units, which greatly reduces byproducts such as single BCB and polymers; (2) Two purification treatments (after cross-coupling and after hydrogenation) completely remove catalyst residues, unreacted monomers and byproducts. Among them, metal catalyst residues are an important cause of premature ring opening of BCB. After purification, catalytic impurities are eliminated, which fundamentally avoids spontaneous prepolymerization during storage and processing.
[0035] 2. Inert atmosphere + hydrogenation process eliminates potential risks from oxidation and unsaturated bonds: Cross-coupling is carried out in an inert gas (N2 / Ar) atmosphere to avoid oxidation of bridging double bonds and BCB units (oxidation products will become active cross-linking sites, causing premature polymerization). Hydrogenation can reduce the unsaturated double bonds of bridging groups to saturated bonds, eliminating the side reactivity of double bonds and ensuring viscosity stability during processing.
[0036] IV. Dielectric performance advantages of dual BCBs.
[0037] The low dielectric loss characteristic of saturated bridging allows the double BCB resin to maintain stable dielectric properties even under high-frequency and high-temperature processing environments, making it suitable for high-end electronic applications.
[0038] In summary, the present application provides a method for preparing low dielectric loss benzocyclobutene resin. This method solves the core processing pain points of traditional BCB through structural design (large steric saturation bridging), and eliminates impurities and side reaction risks through process control (highly selective cross-coupling + purification + hydrogenation), ultimately achieving a significant improvement in the processing stability of benzocyclobutene resin.
[0039] In some alternative embodiments, the amount n1 of the dienyl compound, the amount n2 of the halobenzocyclobutene, and the amount n3 of the acid-binding agent satisfy: n1:n2:n3 = 1:(2.1 to 2.3):(2.2 to 2.5).
[0040] In these embodiments, a dienyl compound, a halobenzocyclobutene, and an acid-binding agent in a molar ratio of 1:(2.1 to 2.3):(2.2 to 2.5) can undergo a sufficient cross-coupling reaction between the dienyl compound and the halobenzocyclobutene under the catalysis of toluene as a solvent and a first catalyst, to obtain a sufficient amount of reactant containing a dibenzocyclobutene diene compound. This introduces a sterically hindered, asymmetric bridging group into the benzocyclobutene, disrupting the planarity and symmetry of the BCB molecule, regulating the ring-opening activity of the bisBCB resin, suppressing viscosity runaway during processing, and improving the processing stability of the bisBCB resin.
[0041] The molar amount n2 of the halobenzocyclobutene can be 2.1, 2.15, 2.2, 2.25 or 2.3.
[0042] The amount of substance n3 of the acid-binding agent can be 2.2, 2.25, 2.3, 2.35, 2.4, 2.45 or 2.50.
[0043] In some alternative embodiments, the amount of the metal compound n4 and the amount of the phosphine-containing ligand n5 satisfy: n4:n5 = 1:(2.4 to 6.0); and / or The amount of substance n4 of the metal compound and the amount of substance n1 of the dienyl compound satisfy the following: n4:n1 = (0.05 to 5.00):100.
[0044] In these embodiments, the molar ratio of a metal compound and a phosphine-containing ligand of 1:(2.4 to 6.0) and the molar ratio of a metal compound and a diene compound of (0.05 to 5.00):100 can introduce a sterically hindered, asymmetric bridging group R1 into benzocyclobutene through the catalytic action of a first catalyst, thereby disrupting the planarity and symmetry of the BCB molecule, regulating the ring-opening activity of the bisBCB resin, suppressing viscosity runaway during processing, and improving the processing stability of the bisBCB resin.
[0045] The amount of substance n5 of the phosphine-containing ligand can be 2.4, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5 or 6.0.
[0046] The amount of substance n4 of the metal compound can be 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 1.00, 2.00, 3.00, 4.00 or 5.00.
[0047] In some optional embodiments, the dienyl compound includes at least one selected from the following: dicyclopentadiene, 4-vinyl-1-cyclohexene, 4,4'-divinyl-1,1'-biphenyl, 1,6-divinylnaphthalene, 1,5-divinylnaphthalene, 2,7-divinylnaphthalene, bisphenol A diallyl ether, bisphenol F diallyl ether, 1,2-bis(4-vinylphenyl)ethane, and 1,4-cyclohexanediethanol divinyl ether; and / or The halobenzocyclobutenes include at least one of 4-bromobenzocyclobutene, 4-chlorobenzocyclobutene, and 4-iodobenzocyclobutene; and / or The acid-binding agent includes at least one of pyridine, triethylamine, trimethylamine, sodium bicarbonate, potassium bicarbonate, sodium carbonate, and potassium carbonate; and / or The metal compound includes at least one of palladium chloride, rhodium chloride, palladium acetate, palladium dichloride of bis(triphenylphosphine), platinum chloride, platinum chlorate, palladium methacrylate, and bis(tributylphosphine)platinum chloride; and / or The phosphine-containing ligand is triphenylphosphine and / or tris(o-methylphenyl)phosphine; and / or The second catalyst includes at least one of the following: aluminum / nickel catalytic system, metallocene catalyst, platinum catalyst, rhodium catalyst, palladium catalyst, and transition metal catalyst supported on a support.
[0048] In these embodiments, dienyl compounds comprising at least one of dicyclopentadiene, 4-vinyl-1-cyclohexene, 4,4'-divinyl-1,1'-biphenyl, 1,6-divinylnaphthalene, 1,5-divinylnaphthalene, 2,7-divinylnaphthalene, bisphenol A diallyl ether, bisphenol F diallyl ether, 1,2-bis(4-vinylphenyl)ethane, and 1,4-cyclohexanediethanol divinyl ether are used; halogenated benzocyclobutenes comprising at least one of 4-bromobenzocyclobutene, 4-chlorobenzocyclobutene, and 4-iodobenzocyclobutene are used; and acid-binding agents comprising at least one of pyridine, triethylamine, trimethylamine, sodium bicarbonate, potassium bicarbonate, sodium carbonate, and potassium carbonate are used. Metal compounds, including at least one of palladium chloride, rhodium chloride, palladium acetate, palladium dichloride of bis(triphenylphosphine), platinum chloride, platinum chlorate, palladium methacrylate, and bis(tributylphosphine)platinum chloride, as well as phosphine-containing ligands of triphenylphosphine and / or tri(o-methylphenyl)phosphine, can facilitate a sufficient cross-coupling reaction between dienyl compounds and halobenzocyclobutenes, yielding a sufficient amount of reactants containing bisbenzocyclobutenyl dienes. This allows the introduction of a sterically hindered, asymmetric bridging group R1 into benzocyclobutene, disrupting the planarity and symmetry of the BCB molecule, regulating the ring-opening activity of the bisBCB resin, suppressing viscosity runaway during processing, and improving the processing stability of the bisBCB resin. Furthermore, using a second catalyst, including at least one of an aluminum / nickel catalytic system, a metallocene catalyst, a platinum catalyst, a rhodium catalyst, a palladium catalyst, and a transition metal catalyst supported on a support, can ensure a sufficient hydrogenation reaction, reducing the unsaturated double bonds of the bridging group to saturated bonds, eliminating the side reactivity of the double bonds, and ensuring viscosity stability during the processing of the bisBCB resin.
[0049] It should be noted that the carrier can be activated carbon, diatomaceous earth, or alumina.
[0050] In some alternative embodiments, the mass m1 of the second catalyst and the mass m2 of the bisbenzocyclobutenyl diene compound satisfy the following ratio: m1:m2 = (0.01 to 3.00):100.
[0051] In these embodiments, the second catalyst and the bisbenzocyclobutenyl diene compound in a mass ratio of (0.01 to 3.00):100 can ensure that the hydrogenation reaction proceeds fully, reduce the unsaturated double bonds of the bridging group to saturated bonds, eliminate the side reactivity of the double bonds, and ensure viscosity stability during the processing of the bisBCB resin.
[0052] In some alternative embodiments, the temperature of the cross-coupling reaction is 60°C to 100°C; and / or The hydrogenation reaction is carried out at a temperature of 20°C to 100°C, at a pressure of 0.1 MPa to 7.0 MPa, and for a time of 1 h to 10 h.
[0053] In these embodiments, the cross-coupling reaction at a temperature of 60°C to 100°C allows for a sufficient reaction between the dienyl compound and the halobenzocyclobutene, introducing the sterically hindered, asymmetric bridging group R1 into the benzocyclobutene, disrupting the planarity and symmetry of the BCB molecule, regulating the ring-opening activity of the bisBCB resin, suppressing viscosity runaway during processing, and improving the processing stability of the bisBCB resin. The hydrogenation reaction at a temperature of 20°C to 100°C, a pressure of 0.1 MPa to 7.0 MPa, and a time of 1 h to 10 h allows for the complete reduction of the unsaturated double bonds of the bridging group to saturated bonds, eliminating the side reactivity of the double bonds and ensuring viscosity stability of the bisBCB resin during processing.
[0054] The temperature for this cross-coupling reaction can be 60℃, 61℃, 62℃, 63℃, 64℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, or 100℃.
[0055] The temperature for the hydrogenation reaction can be 20℃, 30℃, 40℃, 50℃, 60℃, 70℃, 80℃, 90℃ or 100℃.
[0056] The pressure for the hydrogenation reaction can be 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa, 1.0 MPa, 1.0 MPa, 2.0 MPa, 3.0 MPa, 4.0 MPa, 5.0 MPa, 6.0 MPa, or 7.0 MPa.
[0057] The hydrogenation reaction can take 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, or 10 hours.
[0058] Based on a general inventive concept, embodiments of this application provide a low dielectric loss bisbenzocyclobutene resin, which is prepared by the method described above, and has a molecular structure as shown in Formula 1. , Formula 1, In Formula 1, the R1 group is , , , , , , , At least one of them.
[0059] The bisbenzocyclobutene resin is achieved based on the above method. The specific steps of the method can be referred to the above embodiments. Since the bisbenzocyclobutene resin adopts some or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, which will not be elaborated here.
[0060] Based on a general inventive concept, embodiments of this application provide a copper-clad laminate, wherein the raw material of the copper-clad laminate includes the aforementioned bisbenzocyclobutene resin, and by mass parts, the raw material of the copper-clad laminate includes: The composition includes: 100 parts of bisbenzocyclobutene resin, 0.6 to 1.5 parts of vinyl coupling agent, 0.01 to 0.20 parts of initiator, and 43 to 51 parts of filler.
[0061] The copper-clad laminate is based on the above-mentioned bisbenzocyclobutene resin. The specific composition of the bisbenzocyclobutene resin can be referred to the above embodiments. Since the copper-clad laminate adopts some or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, which will not be elaborated here.
[0062] It should be noted that 100 parts by weight of bisbenzocyclobutene resin provides a continuous phase basis for copper-clad laminates with intrinsically low dielectric loss, high heat resistance, and low hygroscopicity, avoiding the dielectric performance degradation caused by the use of traditional polar resins such as epoxy resins and cyanate esters. Furthermore, 0.6 to 1.5 parts by weight of vinyl coupling agent can construct the chemical bonding interface between bisbenzocyclobutene resin and filler, while also ensuring compatibility with the crosslinking system of bisbenzocyclobutene resin, guaranteeing excellent dielectric properties of the copper-clad laminate. Additionally, 0.01 to 0.20 parts by weight of initiator can moderately control the ring-opening curing rate of bisbenzocyclobutene resin, reducing the curing temperature of the copper-clad laminate and shortening the production cycle. Moreover, 43 to 51 parts by weight of filler can significantly reduce the coefficient of thermal expansion of the copper-clad laminate, improving its modulus, thermal conductivity, and dimensional stability. Therefore, through the synergistic effect of the substrate, interface, filler, and curing system, this copper clad laminate achieves an excellent balance between low dielectric properties, dimensional stability, heat resistance, processability, and long-term reliability, perfectly meeting the application requirements of high-frequency and high-speed copper clad laminates.
[0063] The mass fraction of the vinyl coupling agent can be 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, or 1.5 parts.
[0064] The mass fraction of the initiator can be 0.01 parts, 0.02 parts, 0.03 parts, 0.04 parts, 0.05 parts, 0.10 parts, 0.15 parts, or 0.20 parts.
[0065] The mass fraction of the filler can be 43, 44, 45, 46, 47, 48, 49, 50, or 51 parts.
[0066] In some alternative embodiments, the vinyl coupling agent includes at least one of vinyltrimethoxysilane, vinyltriethoxysilane, and vinyltriphenoxysilane; and / or The initiator includes at least one of dicumyl peroxide, di-tert-butyl peroxide, and tert-butyl peroxide; and / or The fillers include at least one of the following: silicon dioxide, montmorillonite, magnesium oxide, aluminum oxide, mica powder, barium sulfate, kaolin, silicon nitride, boron nitride, zirconium oxide, aluminum nitride, graphite, titanium dioxide, talc, and iron oxide.
[0067] In these embodiments, the use of a vinyl coupling agent, including at least one of vinyltrimethoxysilane, vinyltriethoxysilane, and vinyltriphenoxysilane, can construct a chemical bonding interface between the bisbenzocyclobutene resin and the filler, while being compatible with the crosslinking system of the bisbenzocyclobutene resin, ensuring the excellent dielectric properties of the copper-clad laminate. Furthermore, the use of an initiator, including at least one of dicumyl peroxide, di-tert-butyl peroxide, and tert-butyl peroxide, can moderately control the ring-opening curing rate of the bisbenzocyclobutene resin, reducing the curing temperature of the copper-clad laminate and shortening its production cycle. Additionally, the use of a filler, including at least one of silica, montmorillonite, magnesium oxide, aluminum oxide, mica powder, barium sulfate, kaolin, silicon nitride, boron nitride, zirconium oxide, aluminum nitride, graphite, titanium dioxide, talc, and iron oxide, can significantly reduce the coefficient of thermal expansion of the copper-clad laminate, improving its modulus, thermal conductivity, and dimensional stability.
[0068] Figure 2 An exemplary schematic diagram of a method for preparing a copper-clad laminate provided in an embodiment of this application is shown; Based on a general inventive concept, such as Figure 2 As shown in the figure, this application provides a method for preparing the copper-clad laminate, the method comprising: S1. Mix bisbenzocyclobutene resin, vinyl coupling agent, initiator and filler in a second organic solvent to obtain resin solution; S2. Impregnate the glass fiber cloth with the resin solution to obtain impregnated glass fiber cloth; S3. The impregnated glass fiber cloth is subjected to solvent removal to obtain impregnated fiber cloth; S4. Bake the impregnated fiber cloth to obtain a semi-cured sheet; S5. The multilayer semi-cured sheets are sequentially stacked and copper foil is attached to obtain the copper-clad laminate precursor; S6. The copper-clad laminate precursor is hot-pressed to obtain a copper-clad laminate.
[0069] This method relates to the preparation method of the copper-clad laminate described above. The specific composition of the copper-clad laminate can be referred to in the above embodiments. Since this method adopts some or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, which will not be elaborated here.
[0070] It should be noted that the copper foil can be attached to both sides of the laminated cured sheet.
[0071] It should be noted that the hot pressing method can be as follows: first, place the copper clad laminate precursor in a hot press at 170°C, then gradually increase the pressure to 2.5MPa according to the adhesive flow of the copper clad laminate precursor, and then evacuate the vacuum to within 50 torr. After pressing for 1 hour, gradually raise the temperature to 210°C and hot press for 5 hours to obtain the copper clad laminate product.
[0072] In some alternative embodiments, the baking temperature is 130°C to 170°C, and the baking time is 4 min to 7 min.
[0073] In these embodiments, baking at a temperature of 130°C to 170°C for 4 to 7 minutes allows the bisbenzocyclobutene resin impregnated in the fiber cloth to undergo ring-opening curing, which facilitates the subsequent stacking of semi-cured sheets and ultimately forms a cured copper-clad laminate product through hot pressing.
[0074] The baking temperature can be 130℃, 135℃, 140℃, 145℃, 150℃, 155℃, 160℃, 165℃ or 170℃.
[0075] The baking time can be 4 min, 4.5 min, 5 min, 5.5 min, 6 min, 6.5 min, or 7.0 min.
[0076] The present application is further illustrated below with reference to specific embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national / industry standards; if there is no corresponding national / industry standard, they are performed according to general international standards, conventional conditions, or conditions recommended by the manufacturer.
[0077] Example 1
[0078] like Figure 1As shown, a method for preparing low dielectric loss bisbenzocyclobutene resin includes: S1. A diene compound, a halobenzocyclobutene, an acid-binding agent, a first catalyst, and toluene are mixed to obtain a mixed raw material; wherein, the first catalyst is a metal compound and a phosphine-containing ligand; the specific process is as follows: In a reaction flask equipped with a stirrer, thermometer, and inert gas, a diene compound, a halobenzocyclobutene, an acid-binding agent, a first catalyst, and an appropriate amount of toluene are added sequentially and mixed to obtain a mixed raw material. S2. Under an inert gas atmosphere, the mixed raw materials undergo a cross-coupling reaction to obtain the reactants; the specific process is as follows: In an inert gas atmosphere, the mixed raw materials are heated to the endpoint temperature of the cross-coupling reaction and reacted. At the same time, the degree of reaction of the cross-coupling reaction is monitored by chromatography to determine the endpoint of the cross-coupling reaction. After the cross-coupling reaction is completed, the reactants are obtained. S4. The reactants are subjected to a first purification process to obtain a bisbenzocyclobutenyl diene compound; the specific process is as follows: The obtained reactants were sequentially washed with water to neutrality, heated for dehydration, filtered, distilled under reduced pressure, crystallized, and filtered again to obtain a bisbenzocyclobutenyl diene compound. S5. In the first organic solvent, the bisbenzocyclobutene diene compound is subjected to a hydrogenation reaction and a second purification treatment sequentially using a second catalyst to obtain a low-dissipation bisbenzocyclobutene resin; the specific process is as follows: The bisbenzocyclobutene diene compound was dissolved in an appropriate amount of toluene, and a second catalyst was added. The mixture was stirred until homogeneous, and then an appropriate amount of hydrogen was introduced to carry out a hydrogenation reaction. After the hydrogenation reaction was completed, the product of the hydrogenation reaction was washed with pure water and distilled under reduced pressure to obtain high-purity, low-dielectric-loss bisbenzocyclobutene resin.
[0079] The amounts of the dienyl compound n1, the amount of the halobenzocyclobutene n2, and the amount of the acid-binding agent n3 satisfy the following: n1:n2:n3 = 1 mol: 2.1 mol: 2.3 mol.
[0080] The amount of substance n4 of the metal compound and the amount of substance n5 of the phosphine-containing ligand satisfy the following: n4:n5 = 0.006 mol: 0.030 mol; The amount of substance n4 of the gold metal compound and the amount of substance n1 of the dienyl compound satisfy the following: n4:n1 = 0.006 mol: 1 mol.
[0081] The type of dienyl compound is dicyclopentadiene; The type of halogenated benzocyclobutene is 4-bromobenzocyclobutene; The acid-binding agent is triethylamine; The metal compound is palladium chloride; The type of phosphine-containing ligand is triphenylphosphine; The second type of catalyst is a palladium catalyst (Pd / C catalyst) supported on activated carbon.
[0082] The mass m1 of the second catalyst and the mass m2 of the bisbenzocyclobutenyl diene compound satisfy the following condition: m1:m2=0.03:100.
[0083] The temperature for the cross-coupling reaction is 75℃; The hydrogenation reaction was carried out at a temperature of 65℃, a pressure of 2.0 MPa, and a time of 2 hours.
[0084] The bisbenzocyclobutenyl diene compound has the structural formula shown in Formula 2.
[0085] Formula 2.
[0086] A low dielectric loss bisbenzocyclobutene resin, prepared by the above method, has a molecular structure as shown in Formula 1. , Formula 1, In Formula 1, the R1 group is .
[0087] Example 2
[0088] Compared to Example 1, the differences in this example are as follows, while the rest are the same:
[0089] The amounts of the dienyl compound n1, the amount of the halobenzocyclobutene n2, and the amount of the acid-binding agent n3 satisfy the following: n1:n2:n3 = 1 mol: 2.2 mol: 2.5 mol.
[0090] The amount of substance n4 of the metal compound and the amount of substance n5 of the phosphine-containing ligand satisfy the following: n4:n5 = 0.01 mol: 0.04 mol; The amount of substance n4 of the gold metal compound and the amount of substance n1 of the dienyl compound satisfy the following: n4:n1 = 0.01 mol: 1 mol.
[0091] The dienyl compound is bisphenol A diallyl ether; The type of halogenated benzocyclobutene is 4-bromobenzocyclobutene; The acid-binding agent is pyridine; The metal compound is palladium chloride; The type of phosphine-containing ligand is triphenylphosphine.
[0092] The second catalyst is a platinum-ruthenium catalyst (platinum metal catalyst) supported on carbon black at a mass ratio of 2:1.
[0093] The mass m1 of the second catalyst and the mass m2 of the bisbenzocyclobutenyl diene compound satisfy the following condition: m1:m2=0.04:100.
[0094] The temperature for the cross-coupling reaction is 85℃; The hydrogenation reaction was carried out at a temperature of 50°C, a pressure of 6.0 MPa, and a time of 4 hours.
[0095] The bisbenzocyclobutenyl diene compound has the structural formula shown in Formula 3.
[0096] Formula 3.
[0097] Dibenzocyclobutene resin has the molecular structure shown in Formula 1. , Formula 1, In Formula 1, the R1 group is .
[0098] Example 3
[0099] Compared to Example 1, the differences in this example are as follows, while the rest are the same: The amounts of the dienyl compound n1, the amount of the halobenzocyclobutene n2, and the amount of the acid-binding agent n3 satisfy the following: n1:n2:n3 = 1 mol: 2.3 mol: 2.5 mol.
[0100] The amount of substance n4 of the metal compound and the amount of substance n5 of the phosphine-containing ligand satisfy the following: n4:n5 = 0.009 mol: 0.054 mol; The amount of substance n4 of the gold metal compound and the amount of substance n1 of the dienyl compound satisfy the following: n4:n1 = 0.009 mol: 1 mol.
[0101] The dienyl compound is 1,2-bis(4-vinylphenyl)ethane; The type of halogenated benzocyclobutene is 4-bromobenzocyclobutene; The acid-binding agent is potassium carbonate; The metal compound is palladium chloride; The type of phosphine-containing ligand is triphenylphosphine.
[0102] The second catalyst is a Raney nickel catalyst (aluminum / nickel catalyst) with an aluminum to nickel mass ratio of 1:1.
[0103] The mass m1 of the second catalyst and the mass m2 of the bisbenzocyclobutenyl diene compound satisfy the following condition: m1:m2=0.04:100.
[0104] The temperature for the cross-coupling reaction is 90℃; The hydrogenation reaction was carried out at a temperature of 50°C, a pressure of 6.0 MPa, and a time of 4 hours.
[0105] The bisbenzocyclobutenyl diene compound has the structural formula shown in Formula 4.
[0106] Formula 4.
[0107] Dibenzocyclobutene resin has the molecular structure shown in Formula 1. , Formula 1, In Formula 1, the R1 group is .
[0108] Example 4
[0109] Compared to Example 1, the differences in this example are as follows, while the rest are the same: The amounts of the dienyl compound n1, the amount of the halobenzocyclobutene n2, and the amount of the acid-binding agent n3 satisfy the following: n1:n2:n3 = 1 mol: 2.3 mol: 2.5 mol.
[0110] The amount of substance n4 of the metal compound and the amount of substance n5 of the phosphine-containing ligand satisfy: n4:n5 = 0.009 mol: 0.05 mol; The amount of substance n4 of the gold metal compound and the amount of substance n1 of the dienyl compound satisfy the following: n4:n1 = 0.009 mol: 1 mol.
[0111] The dienyl compounds are 4-vinyl-1-cyclohexene; The type of halogenated benzocyclobutene is 4-bromobenzocyclobutene; The acid-binding agent is potassium carbonate; The metal compound is palladium chloride; The type of phosphine-containing ligand is triphenylphosphine.
[0112] The second catalyst is a supported metallocene polyethylene catalyst (metallocene catalyst).
[0113] The mass m1 of the second catalyst and the mass m2 of the bisbenzocyclobutenyl diene compound satisfy the following condition: m1:m2=0.100:100.
[0114] The temperature for the cross-coupling reaction is 95℃; The hydrogenation reaction was carried out at a temperature of 50°C, a pressure of 3.0 MPa, and a time of 3 hours.
[0115] The bisbenzocyclobutenyl diene compound has the structural formula shown in Formula 5.
[0116] Formula 5.
[0117] Dibenzocyclobutene resin has the molecular structure shown in Formula 1. , Formula 1, In Formula 1, the R1 group is .
[0118] Example 5
[0119] Based on the bisbenzocyclobutene resin obtained in Example 1, the following operations were further performed: A copper-clad laminate, wherein the raw material of the copper-clad laminate includes bisbenzocyclobutene resin, and the raw material of the copper-clad laminate includes, by weight parts: Dibenzocyclobutene resin: 100 parts, vinyl coupling agent: 0.9 parts, initiator: 0.09 parts, and filler: 50 parts. The raw materials for the copper-clad laminate are mixed in a second organic solvent (butanone) at a mass ratio of 81 parts to form a resin solution.
[0120] The type of vinyl coupling agent is vinyltrimethoxysilane (Anhui Sibao Organosilicon New Materials Co., Ltd.). The initiator is dicumyl peroxide (Hongbaoli Group Co., Ltd.); The filler is silica (Jiangsu Lianrui DQ1040).
[0121] like Figure 2 As shown, a method for preparing a copper-clad laminate includes: S1. Mix bisbenzocyclobutene resin, vinyl coupling agent, initiator and filler in a second organic solvent to obtain resin solution; S2. Impregnate the fiberglass cloth with resin solution to obtain impregnated fiberglass cloth; S3. Remove the solvent from the impregnated glass fiber cloth to obtain the impregnated fiber cloth; the specific process is as follows: The impregnated fiberglass cloth was suspended at room temperature to remove most of the solvent, resulting in the impregnated fiber cloth. S4. Bake the impregnated fiber cloth to obtain a semi-cured sheet; S5. Stack the 10 layers of semi-cured sheets in sequence and attach copper foil to obtain the copper clad laminate precursor; S6. Hot-press the copper-clad laminate precursor to obtain the copper-clad laminate.
[0122] The baking temperature is 160℃ and the baking time is 5 minutes.
[0123] The hot pressing process is as follows: First, place the copper-clad laminate precursor in a hot press at 170°C. Then, gradually increase the pressure to 2.5MPa according to the adhesive flow of the copper-clad laminate precursor, and evacuate to within 50 torr. Then press for 1 hour, and then gradually raise the temperature to 210°C for hot pressing for 5 hours to obtain the copper-clad laminate product.
[0124] Example 6
[0125] Based on the bisbenzocyclobutene resin obtained in Example 2, the following operations were further performed: By weight, the raw materials for copper-clad laminates include: Dibenzocyclobutene resin: 100 parts, vinyl coupling agent: 1.4 parts, initiator: 0.1 parts, and filler: 46 parts. By weight, the raw materials for the copper-clad laminate are mixed in a second organic solvent (butanone) in a weight of 79 parts.
[0126] Example 7
[0127] Based on the bisbenzocyclobutene resin obtained in Example 3, the following operations were further performed: By weight, the raw materials for copper-clad laminates include: Dibenzocyclobutene resin: 100 parts, vinyl coupling agent: 1.2 parts, initiator: 0.11 parts, and filler: 49 parts. The raw materials for the copper-clad laminate are mixed in a second organic solvent (butanone) at a mass ratio of 80 parts to form a resin solution.
[0128] Example 8
[0129] Based on the bisbenzocyclobutene resin obtained in Example 4, the following operations were further performed: By weight, the raw materials for copper-clad laminates include: Dibenzocyclobutene resin: 100 parts, vinyl coupling agent: 1.3 parts, initiator: 0.08 parts, and filler: 41 parts. The raw materials for the copper-clad laminate are mixed in a second organic solvent (butanone) at a mass ratio of 77 parts to form a resin solution.
[0130] Comparative Example 1
[0131] Compared to Example 5, the differences in this comparative example are as follows, while the rest are the same: In the preparation of copper-clad laminates, the prepared bisbenzocyclobutene resin and vinyl coupling agent are not added; instead, polybutadiene resin (Kreville Ricon 130) is added directly. The raw materials for copper-clad laminates, by weight, include: Polybutadiene resin: 100 parts, initiator: 0.2 parts, and filler: 46 parts. By weight, the raw materials for the copper-clad laminate are mixed in a second organic solvent (butanone) in 79 parts by weight to form a resin solution.
[0132] The preparation method of copper-clad laminate is as follows: S1. Mix polybutadiene resin, initiator and filler in a second organic solvent to obtain a resin solution; S2. Impregnate the fiberglass cloth with resin solution to obtain impregnated fiberglass cloth; S3. Remove the solvent from the impregnated glass fiber cloth to obtain the impregnated fiber cloth; the specific process is as follows: The impregnated fiberglass cloth was suspended at room temperature to remove most of the solvent, resulting in the impregnated fiber cloth. S4. Bake the impregnated fiber cloth to obtain a semi-cured sheet; S5. Stack the 10 layers of semi-cured sheets in sequence and attach copper foil to obtain the copper clad laminate precursor; S6. Hot-press the copper-clad laminate precursor to obtain the copper-clad laminate.
[0133] The baking temperature is 150℃ and the baking time is 5 minutes.
[0134] The hot pressing process is as follows: First, place the copper-clad laminate precursor in a hot press at 170°C. Then, gradually increase the pressure to 2MPa according to the adhesive flow of the copper-clad laminate precursor, and vacuum to within 50 torr. Then press for 1 hour, and then gradually raise the temperature to 220°C for hot pressing for 5 hours to obtain the copper-clad laminate product.
[0135] Comparative Example 2
[0136] Compared to Example 7, the differences in this comparative example are as follows, while the rest are the same: Dibenzocyclobutene resin is replaced with a benzocyclobutene diene compound. The raw materials for copper-clad laminates, by parts by weight, include: Dibenzocyclobutenyl diene compound: 100 parts, vinyl coupling agent: 0.8 parts, initiator: 0.13 parts, and filler: 49 parts.
[0137] The preparation method of copper-clad laminate is as follows: S1. Mix polybutadiene resin, vinyl coupling agent, initiator and filler in a second organic solvent to obtain resin solution; S2. Impregnate the fiberglass cloth with resin solution to obtain impregnated fiberglass cloth; S3. Remove the solvent from the impregnated glass fiber cloth to obtain the impregnated fiber cloth; the specific process is as follows: The impregnated fiberglass cloth was suspended at room temperature to remove most of the solvent, resulting in the impregnated fiber cloth. S4. Bake the impregnated fiber cloth to obtain a semi-cured sheet; S5. Stack the 10 layers of semi-cured sheets in sequence and attach copper foil to obtain the copper clad laminate precursor; S6. Hot-press the copper-clad laminate precursor to obtain the copper-clad laminate.
[0138] The baking temperature is 150℃ and the baking time is 5 minutes.
[0139] The hot pressing process is as follows: First, place the copper-clad laminate precursor in a hot press at 170°C. Then, gradually increase the pressure to 2MPa according to the adhesive flow of the copper-clad laminate precursor, and vacuum to within 50 torr. Then press for 1 hour, and then gradually raise the temperature to 220°C for hot pressing for 5 hours to obtain the copper-clad laminate product.
[0140] Comparative Example 3
[0141] Compared to Comparative Example 1, this comparative example differs as follows, while all other aspects remain the same: In the preparation of the copper-clad laminate, the bisbenzocyclobutene resin of Example 1 was combined with butadiene resin (Kreville Ricon 130). The raw materials for the copper-clad laminate, by weight, include: Polybutadiene resin: 50 parts, bisbenzocyclobutene resin of Example 1: 50 parts, initiator: 0.2 parts, and filler: 46 parts. The raw materials for the copper-clad laminate were mixed in a second organic solvent (butanone) in parts by weight to form a resin solution.
[0142] The preparation method of copper-clad laminate is as follows: S1. Polybutadiene resin, bisbenzocyclobutene resin, initiator and filler are mixed in a second organic solvent to obtain a resin solution; S2. Impregnate the fiberglass cloth with resin solution to obtain impregnated fiberglass cloth; S3. Remove the solvent from the impregnated glass fiber cloth to obtain the impregnated fiber cloth; the specific process is as follows: The impregnated fiberglass cloth was suspended at room temperature to remove most of the solvent, resulting in the impregnated fiber cloth. S4. Bake the impregnated fiber cloth to obtain a semi-cured sheet; S5. Stack the 10 layers of semi-cured sheets in sequence and attach copper foil to obtain the copper clad laminate precursor; S6. Hot-press the copper-clad laminate precursor to obtain the copper-clad laminate.
[0143] The baking temperature is 150℃ and the baking time is 5 minutes.
[0144] The hot pressing process is as follows: First, place the copper-clad laminate precursor in a hot press at 170°C. Then, gradually increase the pressure to 2MPa according to the adhesive flow of the copper-clad laminate precursor, and vacuum to within 50 torr. Then press for 1 hour, and then gradually raise the temperature to 220°C for hot pressing for 5 hours to obtain the copper-clad laminate product.
[0145] Comparative Example 4
[0146] Compared to Comparative Example 3, this comparative example differs as follows, while the rest are the same: A vinyl coupling agent is added during the preparation of copper-clad laminates. The raw materials for copper-clad laminates, by weight, include: Polybutadiene resin: 50 parts, bisbenzocyclobutene resin of Example 1: 50 parts, vinyl coupling agent: 1.2 parts, initiator: 0.2 parts, and filler: 46 parts. The raw materials for the copper-clad laminate were mixed in a second organic solvent (butanone) in parts by weight to form a resin solution.
[0147] The preparation method of copper-clad laminate is as follows: S1. Polybutadiene resin, bisbenzocyclobutene resin, vinyl coupling agent, initiator and filler are mixed in a second organic solvent to obtain a resin solution; S2. Impregnate the fiberglass cloth with resin solution to obtain impregnated fiberglass cloth; S3. Remove the solvent from the impregnated glass fiber cloth to obtain the impregnated fiber cloth; the specific process is as follows: The impregnated fiberglass cloth was suspended at room temperature to remove most of the solvent, resulting in the impregnated fiber cloth. S4. Bake the impregnated fiber cloth to obtain a semi-cured sheet; S5. Stack the 10 layers of semi-cured sheets in sequence and attach copper foil to obtain the copper clad laminate precursor; S6. Hot-press the copper-clad laminate precursor to obtain the copper-clad laminate.
[0148] The baking temperature is 150℃ and the baking time is 5 minutes.
[0149] The hot pressing process is as follows: First, place the copper-clad laminate precursor in a hot press at 170°C. Then, gradually increase the pressure to 2MPa according to the adhesive flow of the copper-clad laminate precursor, and vacuum to within 50 torr. Then press for 1 hour, and then gradually raise the temperature to 220°C for hot pressing for 5 hours to obtain the copper-clad laminate product.
[0150] Relevant experimental and effect data: The performance parameters of the copper-clad laminates of Examples 5 to 8 and Comparative Examples 1 to 2 were statistically analyzed, and the results are shown in Table 1. The test methods for each performance parameter are as follows: (1) Glass transition temperature Tg: Dynamic thermomechanical analysis (DMA) was used to determine the DMA method specified in 2.4.24.4 of IPC-TM-650; (2) Dielectric constant Dk and dielectric loss Df: SPDR method was used to test 10GHz data according to the method specified in IEC 61189-2-721; (3) CTE (Z-axis expansion coefficient): tested according to the method specified in 2.4.24.5 of IPC-TM-650; (4) Peel strength: the peel strength of the metal capping layer was tested according to the experimental conditions of "thermal stress" in the method specified in 2.4.8 of IPC-TM-650.
[0151] Table 1 Performance parameters of copper-clad laminates obtained from the examples and comparative examples
[0152] As shown in Table 1, the method for preparing low dielectric loss bisbenzocyclobutene resin provided in this application solves the core processing pain points of traditional BCB through structural design (large steric saturation bridging + liquefaction), and eliminates impurities and side reaction risks through process control (highly selective coupling + purification + hydrogenation), ultimately achieving a significant improvement in the processing stability of benzocyclobutene resin. Furthermore, a copper-clad laminate product with good heat resistance, dielectric properties, peel strength, and dimensional stability can be obtained, and this copper-clad laminate product can meet the application requirements of high-frequency and high-speed copper-clad laminates.
[0153] Compared to Example 5, the copper-clad laminate prepared by using polybutadiene resin with a flexible backbone as a hydrocarbon resin in Comparative Example 1 has poorer heat resistance, dielectric properties, peel strength, and dimensional stability.
[0154] Compared to Example 7, Comparative Example 2 directly used bisbenzocyclobutene compounds that had not undergone hydrogenation. The heat resistance, dielectric properties, peel strength, and dimensional stability of the copper-clad laminate prepared were similar to those of the Example. However, due to the residual double bonds in the bisbenzocyclobutene compounds, the viscosity of the copper-clad laminate was prone to sudden increase during the preparation stage, resulting in uneven material distribution within the copper-clad laminate. This made it prone to oxidation during storage and use, increasing the loss of dielectric properties and causing the dielectric properties of the copper-clad laminate to deteriorate during long-term use.
[0155] Compared to Comparative Example 1, Comparative Example 3 uses polybutadiene resin with a flexible main chain and bisbenzocyclobutene resin of Example 1 as the main structural components, which can increase the rigidity and crosslinking density of the cured product. The heat resistance, peel strength and dimensional stability of the prepared copper-clad laminate are improved, but it still cannot reach the performance level of the copper-clad laminate of the embodiment of this application. Compared to Comparative Example 3, Comparative Example 4 added a vinyl coupling agent, which can enhance the interfacial bonding force between the filler and the resin, thereby improving the heat resistance, peel strength and dimensional stability of the copper clad laminate. However, it still cannot reach the performance level of the copper clad laminate in the embodiments of this application.
[0156] In summary, the embodiments of this application provide a method for preparing low dielectric loss bisbenzocyclobutene resin. This method solves the core processing pain points of traditional BCB through structural design (introduction of sterically hindered saturated bridging group R1), and eliminates impurities and side reaction risks through process control (highly selective cross-coupling + purification + hydrogenation), ultimately achieving a significant improvement in the processing stability of benzocyclobutene resin.
[0157] In addition, this application provides a method for preparing low dielectric loss bisbenzocyclobutene resin, which has the following advantages: 1. The bisbenzocyclobutene resin prepared by this method has low molecular polarity and excellent dielectric properties: the bisbenzocyclobutene resin contains short-chain alkyl and polycyclic ring structures. At the same time, the cross-linked network structure of rigid structures such as benzene rings and aliphatic rings and flexible short-chain alkyl groups in the bisbenzocyclobutene resin can provide excellent heat resistance and mechanical properties for copper clad laminates.
[0158] 2. The bisbenzocyclobutene resin prepared by this method uses benzocyclobutene as the reactive group. It needs to undergo a cross-linking reaction at 160°C or above without the action of an initiator. Therefore, it can exist stably at room temperature and has good storage stability.
[0159] 3. The bisbenzocyclobutene resin prepared by this method has good flowability and is easily soluble in solvents such as ketones, toluene, and xylene. It also has good compatibility with other resins and fillers and is easy to process.
[0160] 4. The bisbenzocyclobutene resin prepared by this method can be combined with a vinyl coupling agent. When applied to copper clad laminates, the vinyl coupling agent can effectively increase the interfacial bonding force between the hydrocarbon resin (bisbenzocyclobutene resin) and the filler, thereby improving the mechanical properties of the copper clad laminate. In addition, thanks to the low dielectric loss liquid characteristics of the bisbenzocyclobutene resin, the copper clad laminate has excellent heat resistance, dimensional stability, dielectric properties and toughness.
[0161] 5. Using the bisbenzocyclobutene resin prepared by this method as raw material, the copper-clad laminate prepared has excellent comprehensive properties: dielectric constant of 2.51 to 2.55, dielectric loss of 0.0009 to 0.001 at 10 GHz, glass transition temperature of 231℃ to 243℃, peel strength of 1.38 N / mm to 1.47 N / mm, and coefficient of thermal expansion (CTE) of 2.1% to 2.4%.
[0162] 6. Since this method removes the double bond of the dibenzocyclobutene compound through hydrogenation, it can avoid oxidation and yellowing of the copper clad laminate during storage or use, thus giving the copper clad laminate stable dielectric properties.
[0163] 7. The overall preparation process of this method is easy to operate, and the copper-clad laminate prepared using the bisbenzocyclobutene resin obtained by this method as raw material has good heat resistance, dielectric properties, peel strength and dimensional stability. It is suitable for the field of high-performance printed circuit boards and can meet the application requirements of high-frequency and high-speed copper-clad laminates.
[0164] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed in this application.
Claims
1. A method for preparing low dielectric loss bisbenzocyclobutene resin, characterized in that, The method includes: A diene compound, a halobenzocyclobutene, an acid-binding agent, a first catalyst, and toluene are mixed to obtain a mixed feedstock; wherein, the first catalyst is a metal compound and a phosphine-containing ligand; In an inert gas atmosphere, the mixed raw materials are subjected to a cross-coupling reaction to obtain reactants; The reactants were subjected to a first purification process to obtain a bisbenzocyclobutenyl diene compound. In a first organic solvent, the bisbenzocyclobutene diene compound is subjected to a hydrogenation reaction and a second purification treatment using a second catalyst to obtain a low-dielectric-loss bisbenzocyclobutene resin.
2. The method according to claim 1, characterized in that, The amount of the dienyl compound n1, the amount of the halobenzocyclobutene n2, and the amount of the acid-binding agent n3 satisfy the following: n1:n2:n3 = 1:(2.1 to 2.3):(2.2 to 2.5).
3. The method according to claim 1, characterized in that, The amount of the metal compound, n4, and the amount of the phosphine-containing ligand, n5, satisfy: n4:n5 = 1:(2.4 to 6.0); and / or The amount of substance n4 of the metal compound and the amount of substance n1 of the dienyl compound satisfy the following: n4:n1 = (0.05 to 5.00):
100.
4. The method according to claim 1, characterized in that, The dienyl compounds include at least one selected from the following: dicyclopentadiene, 4-vinyl-1-cyclohexene, 4,4'-divinyl-1,1'-biphenyl, 1,6-divinylnaphthalene, 1,5-divinylnaphthalene, 2,7-divinylnaphthalene, bisphenol A diallyl ether, bisphenol F diallyl ether, 1,2-bis(4-vinylphenyl)ethane, and 1,4-cyclohexanediethanol divinyl ether; and / or The halobenzocyclobutenes include at least one of 4-bromobenzocyclobutene, 4-chlorobenzocyclobutene, and 4-iodobenzocyclobutene; and / or The acid-binding agent includes at least one of pyridine, triethylamine, trimethylamine, sodium bicarbonate, potassium bicarbonate, sodium carbonate, and potassium carbonate; and / or The metal compound includes at least one of palladium chloride, rhodium chloride, palladium acetate, palladium dichloride of bis(triphenylphosphine), platinum chloride, platinum chlorate, palladium methacrylate, and bis(tributylphosphine)platinum chloride; and / or The phosphine-containing ligand is triphenylphosphine and / or tris(o-methylphenyl)phosphine; and / or The second catalyst includes at least one of the following: aluminum / nickel catalytic system, metallocene catalyst, platinum catalyst, rhodium catalyst, palladium catalyst, and transition metal catalyst supported on a support.
5. The method according to claim 1, characterized in that, The mass m1 of the second catalyst and the mass m2 of the bisbenzocyclobutenyl diene compound satisfy the following condition: m1:m2 = (0.01 to 3.00):
100.
6. The method according to claim 1, characterized in that, The temperature for the cross-coupling reaction is 60°C to 100°C; and / or The hydrogenation reaction is carried out at a temperature of 20°C to 100°C, at a pressure of 0.1 MPa to 7.0 MPa, and for a time of 1 h to 10 h.
7. A low dielectric loss bisbenzocyclobutene resin, characterized in that, The bisbenzocyclobutene resin is prepared by the method according to any one of claims 1 to 6, and the bisbenzocyclobutene resin has the molecular structure shown in Formula 1. , Formula 1, In Formula 1, the R1 group is , , , , , , , At least one of them.
8. A copper-clad laminate, characterized in that, The raw material of the copper-clad laminate includes the bisbenzocyclobutene resin as described in claim 6. By mass parts, the raw material of the copper-clad laminate includes: The composition includes: 100 parts of bisbenzocyclobutene resin, 0.6 to 1.5 parts of vinyl coupling agent, 0.01 to 0.20 parts of initiator, and 43 to 51 parts of filler.
9. The copper-clad laminate according to claim 8, characterized in that, The vinyl coupling agent includes at least one of vinyltrimethoxysilane, vinyltriethoxysilane, and vinyltriphenoxysilane; and / or The initiator includes at least one of dicumyl peroxide, di-tert-butyl peroxide, and tert-butyl peroxide; and / or The fillers include at least one of the following: silicon dioxide, montmorillonite, magnesium oxide, aluminum oxide, mica powder, barium sulfate, kaolin, silicon nitride, boron nitride, zirconium oxide, aluminum nitride, graphite, titanium dioxide, talc, and iron oxide.
10. A method for preparing the copper-clad laminate according to claim 7 or 8, characterized in that, The method includes: Dibenzocyclobutene resin, vinyl coupling agent, initiator and filler are mixed in a second organic solvent to obtain resin solution; The glass fiber cloth is impregnated with the resin solution to obtain impregnated glass fiber cloth; The impregnated glass fiber cloth is subjected to solvent removal to obtain impregnated fiber cloth; The impregnated fiber cloth is baked to obtain a semi-cured sheet; The multi-layered semi-cured sheets are sequentially stacked and copper foil is attached to obtain the copper-clad laminate precursor. The copper-clad laminate precursor is hot-pressed to obtain the copper-clad laminate; The baking temperature is 130°C to 170°C, and the baking time is 4 min to 7 min.